The supergiant amphipod Alicella gigantea may inhabit over half of the world’s oceans - Paige J. Maroni; Yakufu Niyazi; Alan Jamieson (Royal Society Open Science)
The deep-sea amphipod Alicella gigantea Chevreux, 1899, currently known as the world’s largest amphipod, inhabits depths of the lower abyssal and upper hadal zones. Historically, it has been sampled or observed in situ infrequently relative to other deep-sea amphipods, suggesting low population densities and providing a sense of rarity. Consequently, little is known about the demography, genetic variation and population dynamics of A. gigantea, with only seven studies having published DNA sequence data. As more records emerge from across the vastness of the deep sea, and from depths beyond most conventional sampling, there is an ever-growing body of evidence to show that A. gigantea should be considered far from rare. In this study, we compile 195 records of A. gigantea from 75 locations worldwide and use two mitochondrial genes and one nuclear gene (16S, COI and 28S) to explore their distribution patterns across all oceans and discuss the species history throughout geological time. Our results show that this species may occupy around 59% of the world’s oceans, indicating that the infrequently collected supergiant is not ‘rare’ but instead represents a widely distributed deep-sea amphipod with an exceptional global range.